Basic properties and applications of graded fractal bundles related to Clifford structures: An introduction - Castillo, Alvarado F. L.; Lawrynowicz, J.; Suzuki, O. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Using the central extension of the Cuntz C*-algebra, we study the periodicity for corresponding fractals.